MiR-16 and miR-125b are involved in barrier function dysregulation through the modulation of claudin-2 and cingulin expression in the jejunum in IBS with diarrhoea. Issue 9 (12th January 2017) - Martínez, Cristina; Rodiño-Janeiro, Bruno K; Lobo, Beatriz; Stanifer, Megan L; Klaus, Bernd; Granzow, Martin; González-Castro, Ana M; Salvo-Romero, Eloisa; Alonso-Cotoner, Carmen; Pigrau, Marc; Roeth, Ralph; Rappold, Gudrun; et al.
Abstract : Objective: Micro-RNAs (miRNAs) play a crucial role in controlling intestinal epithelial barrier function partly by modulating the expression of tight junction (TJ) proteins. We have previously shown differential messenger RNA (mRNA) expression correlated with ultrastructural abnormalities of the epithelial barrier in patients with diarrhoea-predominant IBS (IBS-D). However, the participation of miRNAs in these differential mRNA-associated findings remains to be established. Our aims were (1) to identify miRNAs differentially expressed in the small bowel mucosa of patients with IBS-D and (2) to explore putative target genes specifically involved in epithelial barrier function that are controlled by specific dysregulated IBS-D miRNAs. Design: Healthy controls and patients meeting Rome III IBS-D criteria were studied. Intestinal tissue samples were analysed to identify potential candidates by: (a) miRNA-mRNA profiling; (b) miRNA-mRNA pairing analysis to assess the co-expression profile of miRNA-mRNA pairs; (c) pathway analysis and upstream regulator identification; (d) miRNA and target mRNA validation. Candidate miRNA-mRNA pairs were functionally assessed in intestinal epithelial cells. Results: IBS-D samples showed distinct miRNA and mRNA profiles compared with healthy controls. TJ signalling was associated with the IBS-D transcriptional profile. Further validation of selected genes showed consistent upregulation in 75% of genes involved in epithelial barrier function. Bioinformatic analysis of putative miRNA binding sites identified hsa-miR-125b-5p and hsa-miR-16 as regulating expression of the TJ genes CGN (cingulin) and CLDN2 (claudin-2), respectively. Consistently, protein expression of CGN and CLDN2 was upregulated in IBS-D, while the respective targeting miRNAs were downregulated. In addition, bowel dysfunction, perceived stress and depression and number of mast cells correlated with the expression of hsa-miR-125b-5p and hsa-miR-16 and their respective target proteins. Conclusions: Modulation of the intestinal epithelial barrier function in IBS-D involves both transcriptional and post-transcriptional mechanisms. These molecular mechanisms include miRNAs as master regulators in controlling the expression of TJ proteins and are associated with major clinical symptoms.